Pengaruh Store Atmosphere dan In Store Promotion Terhadap Impulse Buying Studi Pada Distro Bandung Super Model. Dinoyo, Kota Malang - FITRI FADHILA; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine how the influence of store atmosphere and in store promotion simultaneously on impulse buying, how does the influence of store atmosphere on impulse buying and to find out how the effect of in store promotion on impulse buying studies on the Bandung Super Model Distro, Dinoyo, Malang. In this study there are 2 (two) independent variables namely store atmosphere and in store promotion and 1 (one) dependent variable, namely impulse buying. The population in this study were people who had shopped at the Bandung Super Model Distro, Dinoyo, Malang City, and the sample in this study was taken using a purposive sampling technique that is sample selection based on certain criteria and obtained a sample size of 60 respondents. Data sources used are primary data and data collection methods used are using questionnaire techniques (Questionnaire). The results of this study state that store atmosphere and in store promotion variables simultaneously influence the impulse buying variable, store atmosphere variables partially have a significant positive effect on impulse buying variables, and in store promotion variables partially have a significant positive effect on impulse buying variables.Keywords: store atmosphere, in store promotion, impulse buying.